Recent trends and perspectives in the application of metal and metal oxide nanomaterials for sustainable agriculture - Hyder, Sajjad (Plant physiology and biochemistry : PPB, 2023)
Copyright © 2023 Elsevier Masson SAS. All rights reserved.